The Clinical Efficacy of Personalized Embryo Transfer Guided by the Endometrial Receptivity Array/Analysis on IVF/ICSI Outcomes: A Systematic Review and Meta-Analysis - Liu, Zhenteng; Liu, Xuemei; Wang, Meimei; Zhao, Huishan; He, Shunzhi; Lai, Shoucui; Qu, Qinglan; Wang, Xinrong; Zhao, Dongmei; Bao, Hongchu (Frontiers in Physiology, 2022)
Objective: To assess the prevalence of displaced window of implantation (WOI) in infertile women, and the clinical utility of personalized embryo transfer (pET) guided by the endometrial receptivity array/analysis (ERA) on IVF/ICSI outcomes. Methods: The protocol was registered at Prospero: CRD42020204237. We systematically searched all published English literature related to the prevalence of WOI displacement and ongoing pregnancy rate/live birth rate in the overall good-prognosis infertile patients (GPP) and/or repeated implantation failure (RIF) patients undergoing IVF/ICSI-ET cycles after ERA test until August 2021. Result(s): 11 published studies were enrolled in the final analysis. The estimate of the incidence of WOI displacement based on ERA was 38% (95%CI 19-57%) in GPP and 34% (95%CI 24-43%) in RIF, respectively. There was no difference in OPR/LBR between patients undergoing routine ET without ERA test and those who following pET with ERA (39.5% vs. 53.7%, OR 1.28, P=0.49, 95%CI 0.92-1.77, I2=0%) in relative GPP. Notably, the meta-analysis revealed that OPR/LBR of patients with RIF undergoing pET who had non-receptive ERA increased to the level of to those undergoing sET with receptive ERA (40.7% vs.49.6%, OR 0.94, P=0.85, 95%CI 0.70-1.26, I2=0%). Conclusion(s): Considering the approximately one third of infertile women could suffered from displaced WOI, the ERA test emerged as a promising tool. Although the present meta-analysis demonstrates that patients with general good-prognosis may not benefit from ERA, pET guided by ERA significantly increases the chances of pregnancy for non-receptive patients with RIF of endometrial origin.